Evaluation of construction systems for social interest housing using the QFD Matriz - Garita Durán, Luis Enrique (2023)
Costa Rica has a housing deficit for its most vulnerable population. There is a lack of information and evaluation of possible construction systems for social interest housing than can improve indicators like scope, cost, quality and construction time in the early phases of a project.An evaluation was conducted with technical and impartial criterion on nine (9) construction systems social housing, specifically for the activities of construction of foundations, walls and finishes, applying the Quality Function Deployment Matrix (QFD)The QFD Matrix transfers user requirements to production requirements using "What's" and "How's" [6]. The final ratings are based on a number of eight hundred ten (810) results based on the variables for two study actors (The contractor and the user).For the contractor, the prefabricated concrete system consisting of columns and horizontal panels, obtained the highest evaluation (236.5), was the system with the best rating.For the user, concrete masonry system, obtained the highest evaluation (196.3)The results are nor absolute, they vary on factors such as the market, regulations, social perception, among others.When a system obtains a better rating, it means that, for the variables considered, for its assigned importance and for the evaluated user,It means that it is the most adequate. It can´t be concluded that in absolute terms, a system with a higher rating is better than the others.